2012
DOI: 10.1007/s10570-012-9722-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of cellulose at the wet-dry interface: I—study of the depolymerization

Abstract: The degradation of cellulose in paper due to the formation of a tideline at the wet-dry interface when paper is suspended in water was explored. SEC/ MALS was used to assess the molar mass, while ICP/ MS, SEM/EDS and CE/UV provided a qualitative and quantitative analysis of the elements and inorganic ions present in the paper. Immediately after the formation of the tideline, no significant depolymerization was observed at the wet-dry interface, despite the accumulation of water soluble brown and/or fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…Additionally, it was observed that when aged together with TL (configuration B), aTL and bTL had a higher HTPA content than when they were aged without TL (configuration A). These results are consistent with our previous study where it was shown that TL clearly affected co-aging samples (in same vial) from other areas in the paper, as monitored by a decrease in their molar mass, but that its own molar mass was affected the least (Jeong et al, 2012). In addition, in configuration C, where direct contact during aging between TL and the other co-aging samples was prevented by placing the TL sample in a separate small glass tube inside the aging vial, the HTPA content of aTL and bTL also increased.…”
Section: Rp-hplc Methods Validationsupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, it was observed that when aged together with TL (configuration B), aTL and bTL had a higher HTPA content than when they were aged without TL (configuration A). These results are consistent with our previous study where it was shown that TL clearly affected co-aging samples (in same vial) from other areas in the paper, as monitored by a decrease in their molar mass, but that its own molar mass was affected the least (Jeong et al, 2012). In addition, in configuration C, where direct contact during aging between TL and the other co-aging samples was prevented by placing the TL sample in a separate small glass tube inside the aging vial, the HTPA content of aTL and bTL also increased.…”
Section: Rp-hplc Methods Validationsupporting
confidence: 93%
“…Hydroperoxides, which are present in high concentration in tidelines are likely to play a role during aging. Oxidation products such as the volatile low molar mass formic and acetic acids, which have been found in large amounts tidelines (Souguir et al, 2008), would catalyze hydrolysis reactions during aging, leading to decreased molar mass of adjacent paper samples, as proposed by Jeong et al (2012). Formic acid in particular would have a crucial part, not only because this acid is the most abundantly present in the tideline, but also because it has been identified recently as very aggressive in vapour phase for paper, being responsible for significant molar mass decrease of cellulose even at room temperature (Tétreault, Dupont, Bégin, & Paris, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic compounds with a high oxidative power such as hydroperoxides, the initial products in free radical autocatalytic oxidation, have been identified in pure cellulose paper [23e25]. Their presence was identified as free hydroperoxides cleaved from the cellulose chain as well as hydroperoxide functionalized cellulose, and their adverse impacts on cellulose degradation were quantified [24,25]. Hydroperoxides are also known to cause discolouration of black and white photographic prints [26,27].…”
Section: Introductionmentioning
confidence: 99%